Noah’s Ark to the Great Commission: Defusing Xenophobia in South Africa - Jonas Sello Thinane (E-Journal of Religious and Theological Studies, 2023)
While incidents of xenophobia, or the occurrence thereof, in some parts of South Africa, are both deplorable and deeply reprehensible, it is important never to ignore the political factors that perpetuate them. Using the interpretive method, this article drew on the literature to present or reinterpret the story of Noah’s Ark in Genesis 6:13-9:29 and the Great Commission of Matthew 28:16-20 in a way that is aimed at defusing xenophobia in South Africa. The Missio Politica as used in this paper provided a missiological framework in which political factors perpetuating xenophobia were seen as an obstacle to the goals of the Missio Dei, particularly the complete redemption of humanity. This paper argued that the continued unlawful imposition of international sanctions against some African countries such as Zimbabwe and, moreover, the lack of refugee camps in countries such as South Africa significantly exacerbates the problem of xenophobia. Consequently, pursuant to defusing xenophobia in South Africa, this paper calls for a renewed mission that includes rejecting unlawful sanctions against African countries and establishing refugee camps not only in South Africa but in all African countries.